Morphological feminization in hermit crabs (family Paguridae) induced by rhizocephalan barnacles - Asami Kajimoto; Aiko Iwasaki; Tsuyoshi Ohira; Kenji Toyota (Zoological Letters)
Abstract Rhizocephalans (Thecostraca: Cirripedia) are parasitic crustaceans that infect a wide range of decapod hosts, including hermit crabs, crabs, and shrimps. These parasites exert profound effects on their hosts, inducing parasitic castration, suppressing the development of secondary sexual characteristics, feminizing male crabs, and altering male behavior to resemble that of females. In the present study, we examined the secondary sexual characteristics of two hermit crab species– Pagurus lanuginosus from Asari (Hokkaido, Japan) on the Sea of Japan coast and Pagurus filholi from Chikura (Chiba, Japan) on the Pacific coast–parasitized by Peltogasterella gracilis and Peltogaster sp., respectively. Specifically, we assessed the presence of secondary pleopods and the length of the right large cheliped. Our findings demonstrate that male P. lanuginosus and P. filholi parasitized by P. gracilis and Peltogaster sp. exhibit morphological changes and characteristics of females, confirming morphological feminization. The magnitude of parasitic effects on morphological feminization varies between the two host species depending on the rhizocephalan genus. Thus, the extent of feminization varies depending on the parasite genus. Notably, different parasite genera induced varying degrees of host modification, even within the same host species. Similarly, the level of feminization caused by a single parasite genus differed between host species. These results highlight the importance of understanding the characteristics of both the hermit crab host and rhizocephalan parasite in developing insights into parasitically induced morphological feminization.